CARBON DIOXIDE ADSORPTION CAPACITY OF INDONEIAN NATURAL ZEOLITE - E. Jasjfi; Edi Janis (Testing Center for Oil and Gas LEMIGAS, 1987)
Natural gas is an important commodity for the economy and development of Indonesia. In addition to its riches in petroleum resources, Indonesia is also endowed with other mineral resources, among which is na- tural zeolite. This paper describes a study made to combine these two resources, the use of zeolite in natural gas processing, specifically for CO, removal by zeolite as solid adsorbent. The experimental results presented in this paper indicate that this Indonesian natural zeolite has good CO, adsorp tion capacity, although the value is only about one half of that obtained from systhetic zeolite. Both zeolites were shown to follow the Langmuir adsorption iso therms and their parameters were established. These and other relevant data are presented in this paper.